Conservation tillage reduces the negative impact of urbanisation on carabid communities. Issue 5 (3rd July 2016) - Tamburini, Giovanni; Pevere, Ines; Fornasini, Niccolò; De Simone, Serena; Sigura, Maurizia; Boscutti, Francesco; Marini, Lorenzo
Abstract: Urban sprawl has been widely recognised as major cause of biodiversity decline across multiple taxonomic levels. Nevertheless, comprehensive studies investigating the effects of landscape urbanisation and farming practices on arthropod biodiversity in agroecosystems are still scarce. We explored the combined effect of urbanisation in the landscape and tillage management (conservation vs. conventional tillage) on predatory carabid beetle communities (Coleoptera: Carabidae) in 10 pairs of winter cereal fields in the agricultural landscape of Udine province (north‐east Italy). Urbanisation (at 750 m scale) strongly decreased carabid activity density, species richness, functional richness and increased functional divergence. We, however, found an interaction between tillage system and the proportion of urban areas in the landscape, i.e., the negative effects of urbanisation on carabid communities were more evident in the fields managed under conventional tillage, while conservation tillage supported more diverse (both taxonomically and ecologically) and abundant beetle communities also in highly urbanised landscapes. We also found that different functional groups differently responded to tillage management. The better local habitat quality provided by conservation tillage may mitigate the negative effects of urbanisation on carabid communities. Our study stresses the importance of considering both local management and landscape composition when planning strategies to support farmland biodiversity.